Community that Sustains Agriculture (CSA) Veredas Vivas: planning and implementation in the community traditional Ponte de Mateus, São Desidério-BA (Citizenship in Action: Extension and Culture Magazine, 2024)
The presente article gather the results of an extension action held in partnership with a professional master's research project, both focused on the planning and implementation of the social technology of solidarity economy Community that Sustains Agriculture (CSA), in partnership with the Community Association of Geraizeiros Residents of Ponte de Mateus, São Desidério-BA. The creation of the CSA is at the same time the result and continuity of the Extension Project Quintais Produtivos, Agroecologia e Segurança Alimentar no Vale do Rio Guará, São Desidério-BA, from which important improvements were obtained in the conditions for carrying out agroextractivist activities, with prominence here to traditional community Geraizeira Ponte de Mateus and the areas with agroecological agroforestry systems implemented. The objective of this work is to plan and support the implementation of social technology, organizing the information and data necessary for the operation of a CSA. The methodological basis followed the premises of the Participatory Rural Diagnosis, with the use of participant observation and conversation circles as tools for participation and dialogue. In the end, for the creation of CSA Veredas Vivas, whose activities began in May, COMGEPOM held an event in Ponte de Mateus to mark its inauguration and start a new phase of activity for the Association and its partnerships.
Keywords: sociobiodiversity; solidarity economy; agroecological agroforestry systems